Analisis Karakteristik Elektrik Limbah Kulit Singkong Berbentuk Pasta Sebagai Sumber Energi Listrik Alternatif Terbarukan - Sutanto, Tri; Supriyanto, Amir; Surtono, Arif (Jurnal Teori dan Aplikasi Fisika, 2018)
The electrical characteristics of cassava peel and cassava can be determined by using a pair of electrode copper (Cu) and zinc (Zn). The measurement of the electrical characteristics of cassava peel had been done using a 5 watt LED load and when the load is released. Cassava peel and cassava are used without fermentation and with fermentation. Electrolyte cell that used consists of 20 cells, which were arranged in series and parallel, with volume + 200 ml for one cell. The maximum power generated cassava peel 5.8597 mW, and 14.1052 mW on cassava. Zn2 electrode (zinc battery used) produces a larger power, which is 5.8597 mW compared with Zn1 (ordinary zinc) is 1.9902 mW. Cassava peel without fermentation produces a larger voltage of 20.76 volts, compared with cassava peel 19.17 volts of fermentation. In cassava peel, circuit cell power in series a larger of 5.8597 volts, compared with circuit power in parallel is 5.7078 volts